In-vitro experiment of nitrogen fixing capacity of indigenous and exogeneous Azotobacter sp at Andisol tea planting area’s - Eko Pranoto; Mieke Rochimi Setiawati (Jurnal Penelitian Teh dan Kina, 2014)
An in-vitro experiment to evaluate total nitrogen content of soil of tea plantation area included with indigenous and exogenous Azotobacter sp have been conducted in the Biology and Soil Biotechnology Laboratory, Padjadjaran University. A completely randomized design with 11 treatments and three replications was used. The treatments were: A (negative control); B (positive control); C (A. Kedelai II); D (A. vinelandii); E (A. N.D.9.3); F (A. Padi); G (VI-1); H (II-1); I (V-2); J (I-1); and K (III-2). Size of microbe inoculated population for each treatment was 1,2 x 1011 CFU/ml. One percent dose was used for sterilized soil originated from the tea plantation area. After five days of incubation period revealed that II-1 Azotobacter sp produced very significantly different in total nitrogen production than the other Azotobacter sp, i.e. 0,8532%. Orthogonal comparisons indicated that indigenous Azotobacter sp had the capacity of nitrogen fixation 7,67% higher than that the capacity of nitrogen fixation of exogenous Azotobacter sp for growth on Andisol soil of tea plantation area with pH of 4,5-5,6. Although, Azotobacter sp is very rarely found in soil with low pH (high acidity), this phenomena indicating that an active biofertilizer of indigenous Azotobacter sp is present in tea plantation area.